2003
DOI: 10.1097/00006324-200302000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity as a Function of Zernike Mode and Level of Root Mean Square Error

Abstract: Increasing the RMS error within any single mode of the normalized Zernike expansion decreases visual acuity in a linear fashion. The slope of the best fitting linear equation varies with Zernike mode. Slopes near the center of the Zernike pyramid are steeper than those near the edge. Although the normalized Zernike expansion parcels RMS error orthogonally, the resulting effects on visual performance as measured by visual acuity are not orthogonal. New metrics of the combined effects of the optical and the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
145
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(155 citation statements)
references
References 5 publications
7
145
0
3
Order By: Relevance
“…They observed that only four patients presented a significant increase in HOAs (mean increase in root mean square error: 0.07 mm). Although this increase in HOAs might reduce visual acuity, 72 they did not detect changes in visual performance. They suggested that symptoms of blurred vision due to hyperglycaemia should be attributed to other factors such as the cerebral cortex or the retina, which might cause subjective symptoms of blurred vision, or that more serious and long-lasting hyperglycaemia would be needed to induce changes in ocular structures large enough to increase aberrations to a level that produces blurred vision.…”
Section: Aberrationsmentioning
confidence: 81%
See 1 more Smart Citation
“…They observed that only four patients presented a significant increase in HOAs (mean increase in root mean square error: 0.07 mm). Although this increase in HOAs might reduce visual acuity, 72 they did not detect changes in visual performance. They suggested that symptoms of blurred vision due to hyperglycaemia should be attributed to other factors such as the cerebral cortex or the retina, which might cause subjective symptoms of blurred vision, or that more serious and long-lasting hyperglycaemia would be needed to induce changes in ocular structures large enough to increase aberrations to a level that produces blurred vision.…”
Section: Aberrationsmentioning
confidence: 81%
“…Although higher-order aberrations (HOAs) make a small contribution (r10%) to the overall wave aberration in the eye, 71 some authors have shown a large effect of degradation in the quality of the retinal image and affect visual acuity. 72 There are factors that may contribute to the change in aberrations, such as ageing, [73][74][75][76][77] accommodation, 78 photoreceptors, 73 pupil size, 71,[79][80][81][82] refractive surgery, 76,[83][84][85] and tear film. 86,87 Even though there are no studies evaluating the impact that these factors could have on HOAs in people with DM, these do have a thicker and more convex lens, [54][55][56] can develop premature cataracts, [9][10][11] and suffer a series of changes associated with lachrymal gland dysfunction and dry eye syndrome.…”
Section: Aberrationsmentioning
confidence: 99%
“…By carrying out visual acuity simulations, other authors have found that aberrations with low orientation dependence had greater effects than those with higher orientation dependence. In dioptric terms, the ratios of visual acuity loss with astigmatism as compared to defocus were 1.1 and 0.8 for high-and low-contrast letters, respectively (Applegate et al, 2003). By using an experimental setup based on adaptive optics, Atchison et al (2009) determined the level of additional aberration at which an individual with normal inherent levels of higher-order ocular aberration becomes aware of blur due to extra defocus or cross-cylinder astigmatism.…”
Section: Tolerances To Uncorrected Astigmatismmentioning
confidence: 99%
“…[70][71][72][73][74][75] It would be expected that, at any pupil diameter, lower levels of HOAs are associated with better distance visual performance, although it is known that similar levels of root-mean-square (RMS) wavefront aberrations distributed between different Zernike coefficients do not necessarily imply equal performance. 76,77 Several studies evaluated the optical performance after hybrid multifocal IOL implantation. Souza and colleagues, 27 Rocha and co-workers 45 and Ortiz and associates 78 studied the optical performance of the AcrySof ReSTOR IOL and compared it with a monofocal IOL.…”
Section: Wavefront Aberrationsmentioning
confidence: 99%